An easy way to prepare reusable rhodamine-based chemosensor for selective detection of Cu2+ and Hg2+ ions. (5th January 2022) - Ozmen, Pinar; Demir, Zehra; Karagoz, Bunyamin
Graphical abstract: Highlights: An easy synthetic routewas demonstrated to obtain rhodamine immobilized P(PVA-co-DVB) microspheres. The resulting microspheres showed sensitive and selective detection against to Hg(II) and Cu(II) ions. LOD and binding constant value of the microspheres were comparable to similar ones in the literature. Small and uniform particle size allowed getting easy stable dispersion in any solvents. Crosslinked nature of the Rhodamine tethered microbeads provided easy handling and regeneration. Abstract: Herein, a simple route was demonstrated for preparation of reusable spherical solid supported rhodamine-based chemosensor and its sensing ability toward metal ions were investigated. First, as solid-support material, aldehyde functional spherical crosslinked Poly (vinyl benzaldehyde- co -divinylbenzene) (P(VBA- co -DVB)) microbeads with a particle size of 2–5 μm were synthesis via precipitation polymerization. Rhodamine hydrazide was then attached to the reachable aldehyde groups (3.05 mmol/g) via imine linkages onto the microbeads. Resulting densely crosslinked almost uniform microspheres with a small particle size can be easily dispersed in any solvent and handled easily during the whole recycling process due to the crosslinked nature of the microbeads. All these features make the rhodamine tethered microspheres an ideal fluorescence chemosensor candidate for the detection of analytes in any solvent. The sensing studies against metal ions revealed that the microspheres show high selectivity and sensitivity fluorescence turn-on and colorimetric response towards Hg 2+ and Cu 2+ ions compare to the other competitor ions in CH3 CN: H2 O (v/v: 80/20, pH: 7.2) medium. The association constant (Ka ) was determined from Benesi-Hildebrand graphics for the microsphere with Hg 2+ and Cu 2+ . Furthermore, the detection limit of the chemosensor was calculated 3.90 × 10 −7 and 5.06 × 10 −7 M for Hg 2+ and Cu 2+, respectively. The fluorescence lifetime of the rhodamine tethered microbeads was also measured as 22.9 ns.